Isolation and Identification of Antibiotic Cryptophycin from Cyanobacteria Nostoc muscorum Isolated from Iraqi Soil - Al-Aarajy,, M.K.; Zeara, S.T.; Al-Mazini, M.A (Iraqi Journal of Aquaculture, 2022)
The study is included isolation and identification of eight species of cyanobacteria from 12 soil samples from Garmat-Ali and Abu-Alkhaseeb in Basrah city. The isolated species have been grown and multiplicated at laboratory condition:Temperature (27±2) ºC and illumination (150-175) Lux for (16:8) hours light : dark cycle. The ability of these species of these species to produce antibiotics against reference strains of the gram positive bacteria, Staphylococcus aureus (NCTC 6571) (gram positive) and the gram negative bacteria, Escherichia coli (NCTC 5933) (gram negative) was tested. Isolate of Nostoc muscorum show inhibition activity with wilde inhibition diameter compared with other isolates. The ability of N.muscorum to secrete antibiotics in the threedifferent fermentation media was tested, the results showed differences in the production of the antibiotiocs between the three different media and the higher productivity was clear in the third medium which showed remarkable activity against bacterial isolates. The antibiotic was purified by using column chromatography technique and assistance the purification of antibiotic was done by using thin layer chromatography (TLC). The produced antibioticswere identified as cryptophycin by determination of: melting point MP), molecular weight and other chemical tests in addition to ultra-violet UV) and infra red spectroscopy (IR). The results of all above tests were showed the similarity between the produced antibiotic aest standard cryptophycin.